INFLUENCE OF CULTURE ON EDUCATION - Elmuradova Surayyo Abdijalilovna (Web of Journals Publishing, 2024)
This article describes the essence of the concept of culture, the influence of culture on education, and the methods of influence of culture on education.
Keywords: education, culture, cultural consciousness, cultural practices, knowledge and values, cultural awareness.